One center's experience with complications during the Wada test. (4th June 2015) - Beimer, Nicholas J.; Buchtel, Henry A.; Glynn, Simon M.
Summary This study aimed to define the number and type of complications associated with the Wada test at an academic medical center for comparison to previous reports. We performed a retrospective review of medical records for patients who underwent the Wada test at the University of Michigan between April 1991 and June 2013. Information was collected regarding the angiography procedure and the immediate postoperative period to assess for both clinical and angiographic complications. A total of 436 patients were identified who underwent the Wada procedure between April 1991 and June 2013, and 431 patients were included in the final analysis. Twenty‐five patients (5.8%) had notable clinical events associated with the Wada test. Nine patients (2.1%) had clinical events meeting criteria for complication, which included seizures, status epilepticus, internal carotid artery vasospasm, inadvertent injection of anesthetic in the external carotid artery, and transient encephalopathy. No complications were associated with significant morbidity or mortality. This retrospective review of patients undergoing the Wada test found significantly fewer associated complications in comparison to previously published studies, with no patients experiencing long‐term morbidity. The Wada test should be considered a safe diagnostic tool for lateralizing language and memory.